Global Food-source Identifier (GFI): Collaborative virtual research environment and shared data catalogue for the foodborne outbreak investigation international community. (March 2021) - Ribeiro Duarte, Ana Sofia; Nielsen, Cecilie Liv; Candela, Leonardo; Valentin, Lars; Aarestrup, Frank M.; Vigre, Håkan
Abstract: The source of a foodborne disease outbreak (FBO) is often difficult to identify, especially in the early phase where interventions would be most efficient. In addition, data on FBOs are mostly scattered in different formats either in national databases and reports or within pathogen-specific or regional reporting networks, both of which are often only accessible to a selected number of individuals. Here, we developed an international, open, shared and searchable data catalogue of past FBOs – the Global Food-source Identifier (GFI). GFI was developed with two objectives: a) to create a collaborative online community of FBO investigators, encouraging the international sharing of data in a harmonized, detailed and comparable manner and b) to support foodborne outbreak investigation worldwide by providing access to detailed records of past outbreaks, which can convey valuable insight into potential 'risk foods' of a detected pathogen. GFI is hosted within a Virtual Research Environment (VRE), which offers additional features to facilitate the collaboration between the outbreak investigators. These features allow document exchange, communication and data visualization and analysis between the VRE members. Based on scientific literature on foodborne outbreaks and discussions within a working group, we selected a total of 46 attributes characterising the outbreak records to be included in the catalogue, aggregated under the four overarching categories causative agent, epidata, food source and report details . Detailed descriptions of the attributes in the catalogue and instructions for harmonized data reporting are available on a wiki page in the VRE. At the time of writing and public launch of GFI, the data catalogue was populated with records of 102 FBOs occurred in Denmark over a period of 12 years (2005–2016) and covering the most frequent pathogens and a broad range of typing methods. The VRE features that enable data analysis, document sharing and communication between members were applied for the graphical representation of the records available in GFI, and for the sharing of results and script files within the VRE. The descriptive analysis included the relationship between the most frequent causative agents and outbreak food sources. Such results can support a risk-based food sampling strategy in the very beginning of a foodborne outbreak investigation. The Global Food-source Identifier is a data catalogue specifically designed to host an international collection of FBO records reported in a detailed and harmonized manner. It is implemented in a virtual research environment that offers key features to facilitate and enhance the global collaboration and data sharing among FBO investigators. Once in active use by the international food safety community, we envisage that GFI will contribute to the success of FBO investigations worldwide. Highlights: Global Food-source Identifier is a public data catalogue of foodborne outbreaks. GFI exists in a virtual research environment that facilitates global collaboration. GFI supports a community with various microbial typing practices. GFI may provide evidence to guide risk-based sampling in outbreak investigations.